Investigating the TLR9 mRNA Expression Level in Different Histological Types of Colorectal Polyps - Rezasoltani, Sama (Asian Pac J Cancer Prev, 2019)
Toll-like receptor 9 (TLR9) is a cellular DNA receptor of the innate immune system which plays a pivotal role in inflammatory response. Recently, changing expression levels of TLR9 has been observed in a wide range of cancer cells; however, there is little information about colorectal polyps. Herein, we assessed the mRNA expression of TLR9 in different colorectal polyp types compared to normal group in order to investigate its expression level during CRC initiation. Fifty-four biopsy samples from colorectal polyp patients and from 20 healthy subjects were collected. The mucosal mRNA expression level of TLR9 gene was identified by real time PCR. Fold change of gene expression was evaluated by 2(-ΔΔct) method. There was a significant relationship between the lower expression of TLR9 gene in the polyp cases compared to normal individuals (P value = 0.0005), Also, decreased TLR9 mRNA expression was obtained in adenomas in contrast to hyperplastic and normal groups (P value = 0.0008). Based on the current results, we hypothesized that aberrant surface expression of TLR9 on tumor cells may promote the growth and invasion of colorectal polyps. Further, TLR9 modulation may have an important impact on the development of novel therapeutic strategies.